Teachers’ Perception on The Aim of Reading Material in an English Textbook - Mona Afersa (Jurnal Ilmiah Pendidikan Scholastic, 2023)
Teaching material takes an important part to the success of teaching and learning. Moreover, Teachers’ perception on the reading materials is essential because it gives valuable input about teaching materials used in the teaching learning process. The main source of teaching materials comes from textbook. This research analyzes reading materials in students’ English textbook for grade XI semester I. The purpose of this research is to describe how are the reading materials in the aspects of aims viewed from the teachers’ perception. Source of the data in this research is divided into two. First is the analysis checklist of reading materials in the students’ English textbook for grade XI semester I filled by three analysts. Two of the analysts are the English teachers at different schools while the other one is the researcher herself. Second is the interview gotten from the teacher who is also one of the analysts in order get more data about the teacher’s perception on the reading material especially about the strength and weakness of the aims of the material. The analyses found that the aims of the reading material fulfill the good criteria of reading aim.